Epidermoid cyst localized in the palatine tonsil - Erol, Keles; Erkan, Kaplama Mehmet; Tolga, Dolen; Bengu, Cobanoglu (My University, 2013)
Epidermoid and dermoid cysts are benign, developmental lesions that can be encountered anywhere in the body. Our literature search did not result in a finding of any report of an epidermoid cyst located in the palatine tonsils. This is a report of a 42-year-old female patient who underwent a tonsillectomy for diagnostic purposes because of an epidermoid cyst arising from the tonsil which was confirmed by histology.
Keywords: Dermoid cyst; epidermoid cyst; palatine tonsil